Job preference of nurse practitioners: A simulation approach - Yin Li; John Howell; Jeannie P. Cimiotti (International Journal of Nursing Studies Advances)
Purpose: Understanding the job preferences of nurse practitioners is crucial for developing policies that attract and retain them in the healthcare workforce, ensuring better healthcare delivery. The aim of this study was to analyze and simulate the job preferences of nurse practitioners, focusing on the impact of various job attributes such as independent practice, practice environment, and salary on their decision-making. Methods: The study used a simulation approach based on a discrete choice experiment survey to predict the job choices of nurse practitioners under different scenarios. The study was conducted in the state of Georgia, USA. 372 survey respondents who were licensed and employed nurse practitioners were included. The likelihood of nurse practitioners choosing a job based on changes in job attributes was analyzed using a hierarchical Bayesian Multinomial Logit model. Results: Nurse practitioners highly value an excellent practice environment and independent practice. A very cohesive interprofessional team and responsive administration significantly influenced job choices. Nurse practitioners might be willing to accept a 10 % salary decrease or a longer commute time for a job with an excellent practice environment. Conversely, they required independent practice for a 10 % salary increase to be attractive. Additionally, the preference for independent practice outweighed the importance of higher salaries and shorter commute time. Conclusion: The study highlights the importance of an excellent practice environment and independent practice in the job preference of nurse practitioners. Healthcare organizations should focus on creating supportive, collaborative work environments and enabling greater autonomy for nurse practitioners. Policymakers should consider revising regulations to expand nurse practitioners' scope of practice.